The impact of the regulatory sandbox on the fintech industry, with a discussion on the relation between regulatory sandboxes and open innovation - Jayoung James Goo; Joo-Yeun Heo (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
As the fintech industry grows around the world, regulatory issues continue to be a hot topic within the industry. To overcome regulatory barriers of the fintech industry, regulatory sandboxes have been adopted. The regulatory sandboxes are beneficial to create a fintech ecosystem, but their effectiveness has not been empirically supported. This study aims to find the expected effects of regulatory sandboxes on fintech venture investments empirically. We conducted an analysis using a country-level comparative research method. To analyze it, we selected nine forerunning countries which have initially adopted regulatory sandboxes. For the purpose of validations, a comparative analysis and a regression analysis were conducted. In the results, we found that the adoption of regulatory sandboxes had very positive influences on the growth of the fintech venture investment. The results implied that regulatory sandboxes may play a vital role in increasing the influx of venture capital into the fintech venture ecosystem by removing regulatory uncertainty. The findings of this research contribute to providing the empirical evidences to policy makers in interpretations of the positive impact of regulatory sandboxes.
Keywords: 650; financial innovation; fintech; investment; regulatory sandbox; venture; venture capital